Nail Psoriasis, the unknown burden of disease. (15th January 2014) - Klaassen, K.M.G.; van de Kerkhof, P.C.M.; Pasch, M.C.
Abstract Background Psoriasis can be found at several different localizations which may be of various impact on patients' quality of life (QoL). One of the easy visible, and difficult to conceal localizations are the nails. Objective To achieve more insight into the QoL of psoriatic patients with nail psoriasis, and to characterize the patients with nail involvement which are more prone to the impact of the nail alterations caused by psoriasis. Method A self‐administered questionnaire was distributed to all members (n = 5400) of the Dutch Psoriasis Association. The Dermatology Life Quality Index (DLQI) and the Nail Psoriasis Quality of life 10 (NPQ10) score were included as QoL measures. Severity of cutaneous lesions was determined using the self‐administered psoriasis area and severity index (SAPASI). Results Patients with nail psoriasis scored significantly higher mean scores on the DLQI (4.9 vs. 3.7, P = <0.001) and showed more severe psoriasis (SAPASI, 6.6 vs. 5.3, P = <0.001). Patients with coexistence of nail bed and nail matrix features showed higher DLQI scores compared with patients with involvement of one of the two localizations exclusively (5.3 vs. 4.2 vs. 4.3, P = 0.003). Patients with only nail bed alterations scored significant higher NPQ10 scores when compared with patients with only nail matrix features. Patients with psoriatic arthritis (PsA) and nail psoriasis experiences more impairments compared with nail psoriasis patients without PsA (DLQI 5.5 vs. 4.3, NPQ10 13.3 vs. 7.0). Females scored higher mean scores on all QoL scores. Conclusion Greater attention should be paid to the possible impact nail abnormalities have on patients with nail psoriasis, which can be identified by nail psoriasis specific questionnaires such as the NPQ10. As improving the severity of disease may have a positive influence on QoL, the outcome of QoL measurements should be taken into account when deciding on treatment strategies.